2018
DOI: 10.23986/afsci.69116
|View full text |Cite
|
Sign up to set email alerts
|

Ramularia collo-cygni: a new pathogen spreading in barley fields in Estonia

Abstract: Ramularia leaf spot (RLS) caused by the fungus Ramularia collo-cygni (Rcc) is affecting barley fields throughout temperate regions worldwide. The first finding of RLS in Estonia was reported on spring barley in 2012 and since then the area of RLS infection has been widening in Estonia. This work has been carried out to monitor the natural infection of Rcc in two winter barley cultivars and to follow artificial fungal infection by a PCR-based assay. Using our approach, we could detect presence of the fungal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Estonya'da iki kışlık arpa çeşidinde Rcc'nin doğal enfeksiyonunu izlemek ve moleküler bazlı testle fungus enfeksiyonunu takip etmek için yapılan bir çalışmada erken büyüme aşamalarında hastalık belirtileri ortaya çıkmadan önce arpa yapraklarında fungal patojeninin varlığı tespit edilebilmiştir. Test edilen iki çeşidin tarla koşullarında Rcc enfeksiyonuna tepkisi farklı bulunmuş olup bu da Rcc'nin gelişimi ve yayılmasında genotip-çevre etkileşiminin olduğunu göstermiştir [68]. R. collo-cygni'nin biyolojisindeki havayla taşınan sporların önemi hala tartışmalı bir konu olsa da araştırmacılar fungusun spor hareketi ile hastalık salgınları arasında yakın bir ilişki bulmuşlardır.…”
Section: Epi̇demi̇yoloji̇si̇unclassified
See 2 more Smart Citations
“…Estonya'da iki kışlık arpa çeşidinde Rcc'nin doğal enfeksiyonunu izlemek ve moleküler bazlı testle fungus enfeksiyonunu takip etmek için yapılan bir çalışmada erken büyüme aşamalarında hastalık belirtileri ortaya çıkmadan önce arpa yapraklarında fungal patojeninin varlığı tespit edilebilmiştir. Test edilen iki çeşidin tarla koşullarında Rcc enfeksiyonuna tepkisi farklı bulunmuş olup bu da Rcc'nin gelişimi ve yayılmasında genotip-çevre etkileşiminin olduğunu göstermiştir [68]. R. collo-cygni'nin biyolojisindeki havayla taşınan sporların önemi hala tartışmalı bir konu olsa da araştırmacılar fungusun spor hareketi ile hastalık salgınları arasında yakın bir ilişki bulmuşlardır.…”
Section: Epi̇demi̇yoloji̇si̇unclassified
“…Mäe ve ark. [68], yabancı otların inokulum kaynağı olabileceğini öne sürmüştür, ancak bu alternatif konukçuların RLS epidemiyolojisindeki rolü tam olarak belirlenmemiştir.…”
Section: Epi̇demi̇yoloji̇si̇unclassified
See 1 more Smart Citation
“…In Estonia, net blotch ( Pyrenophora teres ) and spot blotch ( Cohliobolus sativus ) have been the most common foliar diseases of barley, causing serious yield and quality reduction [ 25 ]. Due to the increasing spread of R. collo-cygni , RLS has become an emerging disease in Estonian barley fields in the recent past [ 26 ]. Genetic studies have revealed a lack of geographical clustering of R. collo-cygni populations, which emphasises the major role of global seed transport in transmitting the pathogen around barley growing countries and also spreading fungicide resistant R. collo-cygni isolates [ 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to predict the capacity of pathogen populations because RLS is very often hidden behind other diseases and the diagnosis of physiological leaf spots [ 44 ]. In 2012, R. collo-cygni was first found in a few spring barley fields in Estonia [ 6 ], but in the growing season of 2015–2016, RLS infection was more widespread and had also spread to winter barley fields [ 26 ].…”
Section: Introductionmentioning
confidence: 99%